Adipose PTEN regulates adult adipose tissue homeostasis and redistribution via a PTEN-leptin-sympathetic loop - Wei Huang; Nicholas J. Queen; Travis B. McMurphy; Seemaab Ali; Lei Cao (Molecular Metabolism, 2019)
Objective: Despite the large body of work describing the tumor suppressor functions of Phosphatase and tensin homologue deleted on chromosome ten (PTEN), its roles in adipose homeostasis of adult animals are not yet fully understood. Here, we sought to determine the role of PTEN in whole-body adipose homeostasis. Methods: We genetically manipulated PTEN in specific fat depots through recombinant adeno-associated viral vector (rAAV)-based gene transfer of Cre recombinase to adult PTENflox mice. Additionally, we used a denervation agent, 6OHDA, to assess the role of sympathetic signaling in PTEN-related adipose remodeling. Furthermore, we chemically manipulated AKT signaling via a pan-AKT inhibitor, MK-2206, to assess the role of AKT in PTEN-related adipose remodeling. Finally, to understand the role of leptin and central signaling on peripheral tissues, we knocked down hypothalamic leptin receptor with a microRNA delivered by a rAAV vector. Results: Knockdown PTEN in individual fat depot resulted in massive expansion of the affected fat depot through activation of AKT signaling associated with suppression of lipolysis and induction of leptin. This hypertrophic expansion of the affected fat depot led to upregulation of PTEN level, higher lipolysis, and induction of white fat browning in other fat depots, and the compensatory reduced fat mass to maintain a set point of whole-body adiposity. Administration of AKT inhibitor MK-2206 prevented the adipose PTEN knockdown-associated effects. 6OHDA-mediated denervation demonstrated that sympathetic innervation was required for the PTEN knockdown-induced adipose redistribution. Knockdown hypothalamic leptin receptor attenuated the adipose redistribution induced by PTEN deficiency in individual fat depot. Conclusions: Our results demonstrate the essential role of PTEN in adipose homeostasis, including mass and distribution in adulthood, and reveal an “adipose PTEN-leptin-sympathetic nervous system” feedback loop to maintain a set point of adipose PTEN and whole-body adiposity. Keywords: PTEN, Leptin, Adipose, Homeostasis, Hypothalamus, Redistribution